IMPLEMENTASI STANDAR PENILAIAN KURIKULUM 2013 PENDIDIKAN KEWARGANEGARAAN UNTUK MEMBENTUK MORAL FEELING SISWA - Wahyudin Fitriyana (Universitas Singaperbangsa Karawang, 2017)
Achievement of learning outcomes of student in the curriculum can be seen from the assessment results.Assessment as the process of collecting and processing information to measure student learning outcomes.The theory in this research is based on permendikbud no. 104/2014 on assessment standards and the formation of moral feeling (Lickona 1992).The population of 720 students class VIII SMP Negeri 2 and 5 Bandung.Sampling using random sampling method. The sample of research is 233 participants. Methods of data collection include observation, interviews, questionnaires, documentation studies and literature studies. The results of this study indicate that (1) the implementation of the standard assessment of curriculum 2013 in SMP Negeri 2 and 5 Bandung in accordance with existing provisions that is based on permendikbud no 104/2014 on assessment standards. Teachers are given guidance in determining the assessment of the outcomes of the learning process. (2) the test result of significant efffect on applying the standard of assessment to